Analisis Jumlah Uang Beredar, Inflasi dan Nilai Aktiva Bersih Reksadana Syariah - Firman Setiawan; Qudziyah Qudziyah (Universitas Islam Lamongan, 2021)
Abstract: Nett asset value (NAV) is a barometer of the performance of sharia mutual funds. The increase in NAV shows that the performance of sharia reksadana is good, and vice versa. Several factors can affect the NAV of Islamic mutual funds, including the money supply and inflation. This study aims to answer the proposed hypothesis that there is a significant effect of the money supply and inflation on the net asset value of sharia mutual funds. The method used is a quantitative method with time-series data. The population in this study is data on the amount of money supply, inflation, and net asset value of sharia mutual funds in Indonesia. The sample is 60 data from January 2015 to December 2019. To process and analyze the data, researchers conducted multiple linear regression tests using the software SPSS 24. It is known that simultaneously the money supply and inflation have a significant effect on the net asset value of Islamic mutual funds. The money supply also has a substantial impact on the net asset value of Islamic mutual funds. However, inflation does not have a significant effect on the net asset value of Islamic mutual funds.